Scale influence in morphometric analysis of the watersheds - Zanata, Marcelo [UNESP]; Pissarra, Teresa C. T. [UNESP]; Arraes, Christiano L.; Rodrigues, Flavia M. [UNESP]; Campos, Sérgio [UNESP] (FapUNIFESP (SciELO), 2011)
In order to verify the different scales in physical analysis of watersheds, the geomorphic quantitative analysis was done to distinguish homogeneous areas within this land unit. The variables studied were the dimensions, drainage pattern and relief characteristics. The study area is the watershed of the Córrego da Cachoeira, São Paulo State, Brazil. The cartographic scale 1:50000 (IBGE) and 1:10000 (IGC) were used to delineate the drainage network and study the morphometric characteristics. The watershed is characterized as an exoreic, fluvial drainage with consequent streams and drainage pattern. The values of the drainage density, frequency of rivers and the ratio of bifurcation are considered low, indicating the formation of the soil on permeable rock. The low values suggested a watershed with relatively mild relief. The detail of the cartography mapping analysed with field study data showed higher values of hydrological compartments and length of the drainage network, reflecting changes in the results obtained on the physical variables analysed.
Influência da escala na análise morfométrica de microbacias hidrográficas
Keywords: Drainage pattern; Morphometry; Official mapping